Sosialisasi Pencegahan dan Penanganan Nyeri Pinggang Bersama Persatuan Wredatama Republik Indonesia (PWRI) - Viyanti, Aulia Nanda; Dhira Rahma Fadila; Saharudin, Adinda Afifah; Nursaputri; Hanan, Salma Zahra Fitria; Srimela, Mary Zahra; Safitri, Khusnul; Wibowo, Embar Arie; Sudaryanto, Wahyu Tri; Supriyadi, Arin; Maghfiroh, Rinna Ainul; Filmasari, Fitri (Forum Kerjasama Pendidikan Tinggi, 2025)
Kelurahan Kroyo, located in Karangmalang District, Sragen Regency, has strategic road access and the majority of its population works in the private sector, agriculture, and as brick craftsmen. However, the physical conditions often leading to heavy physical activity have made health issues, especially low back pain (LBP), a major health concern. LBP, a common problem among the elderly, is often triggered by factors such as aging, poor work habits, and a lack of physical activity. This can decrease the quality of life and productivity within the community. The purpose of this community service program is to provide preventive education and management of LBP through health counseling and physiotherapy interventions to the community of Kelurahan Kroyo, particularly members of the Persatuan Wredatama Republik Indonesia (PWRI). The participant in this activity is the PWRI Branch of Karangmalang, which has 26 elderly members. The implementation method of this program was carried out in three stages: preparation (coordination with the village administration and the village midwife), execution (health counseling and interactive discussions), and evaluation (post-test to assess participants' understanding). The results of the activity show an increase in participants' knowledge about the prevention and management of LBP, with the pre-test average score being 36.7% and the post-test increasing to 63.3%. This activity not only enhanced health awareness but also provided practical skills that can be applied in daily life, such as stretching exercises and proper posture. Through this community service, it is hoped that PWRI members will be able to reduce LBP complaints and lead a healthier and more productive life.